2021
DOI: 10.1186/s12955-021-01683-2
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life in Chinese juvenile idiopathic arthritis patients: psychometric properties of the pediatric quality of life inventor generic core scales and rheumatology module

Abstract: Background Juvenile idiopathic arthritis (JIA) may seriously affects patients’ quality of life (QoL), but it was rarely focused and studied in China, so we explore JIA children’s QoL using Chinese version of the PedsQL4.0 Generic Core and PedsQL3.0 Rheumatology Module scale, and analyzed the psychometric properties of these two Scales among Chinese JIA children. Methods We recruited 180 JIA patients from Children's Hospital Affiliated to Capital In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, rare conditions pose challenges to the translation of a HRQOL questionnaire, why the standard procedure may need practical adaptation, such as producing less forward-backward translations [ 35 , 36 ]. Moreover, many HRQOL measures have been developed in English [ 35 ], and have been translated from English into Chinese [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The EA-QOL questionnaires were developed in the Swedish language, and Sweden is a low-population country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, rare conditions pose challenges to the translation of a HRQOL questionnaire, why the standard procedure may need practical adaptation, such as producing less forward-backward translations [ 35 , 36 ]. Moreover, many HRQOL measures have been developed in English [ 35 ], and have been translated from English into Chinese [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The EA-QOL questionnaires were developed in the Swedish language, and Sweden is a low-population country.…”
Section: Discussionmentioning
confidence: 99%
“…Then, studies have demonstrated overall acceptable psychometric performance of the EA-QOL questionnaires among children with EA in Turkey, Poland and the Netherlands [ 20 , 21 , 22 ]. Many QOL/HRQOL questionnaires have been translated from English to Chinese, and the Chinese version of the questionnaires has achieved satisfactory validity and reliability [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In order to increase knowledge of HRQOL of children with EA in China, it is central to investigate the psychometric properties of the EA-QOL questionnaires among Chinese families of children with EA.…”
Section: Introductionmentioning
confidence: 99%